The Sardine In The Network: Metaphorical Analysis Of Connectivity And Saturation Dynamics In Digital Ecosystems - Hafida Slimani; Rachid Saim (The Journal of Studies in Language, Culture and Society)
The purpose of this study is to explore the sardine metaphor in describing digital networks and analyze its effectiveness in explaining congestion and connectivity in modern computer systems. The research question focuses on how this metaphor can simplify the understanding of the network overload problem and make a complex concept more understandable to nonexperts. The research methodology includes a historical review of the sardine metaphor, followed by an examination of case studies in which this metaphor has been used in scientific and technical outreach contexts. The research instrument was a qualitative analysis of the metaphor's application context and a critical evaluation of its strengths and limitations. The results show that the sardine metaphor effectively simplifies the understanding of the network congestion problem and makes complex concepts understandable to nonspecialists. However, certain limitations have been identified, particularly regarding the accuracy and evolution of digital technology. The study concludes that, while the sardine metaphor is useful in some contexts, it requires continuous adaptation to remain relevant in the context of rapid advances in digital technology. This study suggests directions for future research, including the development of new metaphors that could provide new perspectives for communicating technological issues.